VALUE CHAIN GOVERNANCE FOR SMOKED FISH PRODUCTS IN THE NORTH COAST OF CENTRAL JAVA - Wicaksana, Indrajit; Nurmalina, Rita; Suprehatin (Jurnal Manajemen dan Agribisnis, 2020)
The seafood and aquaculture industry in Indonesia is much less vertically coordinated. However, there are trends towards coordination in fishery value chains through processing and distribution to retail and food service customers. This study aims to examine the governance of the smoked fish value chains in the North Coast of Central Java. The study used the survey data of 52 actors along the smoked fish value chains in the North Coast of Central Java, including fisherman in Demak and Rembang regencies, various types of middleman, processor, and retailers in Semarang. The data was analyzed using value chain mapping and governance analyses. The results showed that the actors involved in the smoked fish value chains consist of fishermen, wholesalers, collectors, processors, retailers, food stalls, and restaurants. Each actor has different activities in their role to add value to differentiate smoked fish products. The results also showed that the types of value chain governance of smoke fish in the North Coast of Central Java leads to relational governance with the complex and interdependent transactions. Keywords: aquaculture, coordination, fisherman, fishery products, relational